Cellular Plasticity in Response to Suppression of Storage Proteins in the Brassica napus Embryo. Issue 7 (30th April 2020) - Rolletschek, Hardy; Schwender, Jörg; König, Christina; Chapman, Kent D.; Romsdahl, Trevor; Lorenz, Christin; Braun, Hans-Peter; Denolf, Peter; Van Audenhove, Katrien; Munz, Eberhard; Heinzel, Nicolas; Ortleb, Stefan; et al.
Abstract : Suppressing the genes encoding napin and cruciferin leads to an increase in oleosin accumulation and a reorganization of the intracellular architecture in the developing embryo of oilseed rape. Abstract: The tradeoff between protein and oil storage in oilseed crops has been tested here in oilseed rape ( Brassica napus ) by analyzing the effect of suppressing key genes encoding protein storage products (napin and cruciferin). The phenotypic outcomes were assessed using NMR and mass spectrometry imaging, microscopy, transcriptomics, proteomics, metabolomics, lipidomics, immunological assays, and flux balance analysis. Surprisingly, the profile of storage products was only moderately changed in RNA interference transgenics. However, embryonic cells had undergone remarkable architectural rearrangements. The suppression of storage proteins led to the elaboration of membrane stacks enriched with oleosin (sixfold higher protein abundance) and novel endoplasmic reticulum morphology. Protein rebalancing and amino acid metabolism were focal points of the metabolic adjustments to maintain embryonic carbon/nitrogen homeostasis. Flux balance analysis indicated a rather minor additional demand for cofactors (ATP and NADPH). Thus, cellular plasticity in seeds protects against perturbations to its storage capabilities and, hence, contributes materially to homeostasis. This study provides mechanistic insights into the intriguing link between lipid and protein storage, which have implications for biotechnological strategies directed at improving oilseed crops.